STUDI TENTANG INTERVENSI ETIKA DAN PENINGKATAN MORAL MAHASISWA - Najmudin Najmudin; Wiwiek R. Adawiyah (Jurnal Bisnis dan Ekonomi, 2011)
The purpose of the study is to analyze the moral development of students from AccountingDepartment and Management Department at Economic Faculty Unsoed. This study is a surveywith the methods of collecting data using questionnaires. The population is a student at theFaculty of Economics, University of Jenderal Sudirman. The sample was taken by purposivesampling technique and sampling considerations which selected students who are still active inthe International Accounting Department and International Management Department. Theinstrument used to measure the moral development of students was defining issue test (DIT).Research findings indicate that students who have attended ethical class have better moraldevelopment as compared to those who have not taken the course. Moreover Accountingstudents have not better moral development as compared to students from ManagementDepartment. Based on the findings, it is recommended that ethics should be offered to economicsstudents since it appears to affect student’s moral development. In addition, the inclusion ofethics as a course must be offered to other departments too, as the case of accounting departmentand management department.Key Words: Ethic, Moral Development, DIT